Healing Wounds with Honey - Tiffany Koenig; Joni Cramer Roh (Undergraduate Research Journal for the Human Sciences, 2016)
Honey has been used to treat wounds throughout the ages, even before bacteria were discovered. This research paper will discuss the healing phases and how honey plays a role in each phase. It also describes the proposed antibacterial, anti-inflammatory, and antioxidant mechanisms of actions and the clinical evidence of the efficacy of honey in a variety of acute and chronic wound types ranging from diabetic ulcers to Methicillin-resistant staphylococcus aureus. (MRSA) The use of honey as a wound-healing agent has many attributes that make it an option when treating athletes. Among the benefits discussed are honey's properties, safety, and effectiveness. These benefits make honey not only a viable, but an optimal treatment option in modern wound care. The databases that was used to collect the 18 articles that will be discuss was MEDLINE Complete and SPORTDiscus. This review reveals the possible usage of honey in athletic health care, but further research is recommended.
Keywords: Healing; Honey